2003
DOI: 10.1159/000072472
|View full text |Cite
|
Sign up to set email alerts
|

Pathologically Proven Cavernous Angiomas of the Brain following Radiation Therapy for Pediatric Brain Tumors

Abstract: Lesions consistent with cavernous angiomas (CAs) of the brain are sometimes seen on MRI scans of the brains of patients who received radiation therapy for brain tumors as children. The lesions appear years later within brain tissue that was included in radiation fields. It is unclear whether these MRI-detected lesions are true CAs or a pathological variant. This study reports the clinical, radiographical, and pathological findings in 3 cases of radiation-induced CAs of the brain. From 1995 to 1997, 3 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 8 publications
2
54
0
3
Order By: Relevance
“…Unfortunately, progressively reduced intellect and other cognitive and central neurological deficits [26][27][28][29][30][31][32][33] are a none too uncommon consequence of this treatment combination, especially in the young developing brain. These consequences even include alterations in the sleep-wake cycle that persist long into adulthood, up to 30 years post-treatment, including the requirement for almost one full hour more of sleep per day 38 ; and the frequent formation of gross anatomical defects, like cavernomas and cavernous angiomas, that occasionally require later surgical excision due to seizures, bleeding and other problems [39][40][41] . Some evidence exists that reduced dose radiotherapy may lessen the risk and extent of adverse effects 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, progressively reduced intellect and other cognitive and central neurological deficits [26][27][28][29][30][31][32][33] are a none too uncommon consequence of this treatment combination, especially in the young developing brain. These consequences even include alterations in the sleep-wake cycle that persist long into adulthood, up to 30 years post-treatment, including the requirement for almost one full hour more of sleep per day 38 ; and the frequent formation of gross anatomical defects, like cavernomas and cavernous angiomas, that occasionally require later surgical excision due to seizures, bleeding and other problems [39][40][41] . Some evidence exists that reduced dose radiotherapy may lessen the risk and extent of adverse effects 42 .…”
Section: Discussionmentioning
confidence: 99%
“…They attribute the development of hemorrhages to disruption and alteration of capillary integrity by irradiation and also to lesions remarkably similar to cavernous angiomas 8,14 . Additional reports support the role of radiation injury in the development of de novo cavernomas 2,[4][5][6][7][8][9][10][11]13 . On considering the risk factors involved in the development of radiation induced cavernomas and, in a similar way to those reported in the formation of second malignant neoplasms, two group of risk factors have to be taken into account: (a) therapy related factors, such as radiation therapy, dose, associated use of chemotherapy etc., and (b) factors inherent to the patients, such as age, immune status, genetic factors etc 1,16 .…”
Section: Formation Of Cavernomas After Radiotherapymentioning
confidence: 90%
“…In 1994, Ciricillo et al first suggested that cavernomas could be induced by irradiation 5 . Since then, some reports have attributed the formation of cavernomas to the treatment with radiotherapy 1,2,4,[6][7][8][9][10][11]13,14 . In several instances, cavernomas manifested with spontaneous cerebral hemorrhage 2 while, in others, the lesions were discovered during the evaluation of new symptoms unrelated to the initial brain tumor 4,6,10,11,13 .…”
Section: Introductionmentioning
confidence: 99%
“…They are well known to develop after cranial irradiation [6,7]. Baumgartner et al reported development of cavernous angiomas 7 -19 years after cranial irradiation [6].…”
Section: Case Reportmentioning
confidence: 99%
“…They are well known to develop after cranial irradiation [6,7]. Baumgartner et al reported development of cavernous angiomas 7 -19 years after cranial irradiation [6]. In a literature review of radiation-induced cavernomas, Nimjee et al found reports in the literature of 76 patients with radiation-induced cavernomas with a mean latency of 8.9 years following treatment [7].…”
Section: Case Reportmentioning
confidence: 99%